Investigation of the effect of playing sports on social appearance anxiety - KAYHAN, RECEP FATİH (My University, 2023)
Social appearance anxiety plays a key role in the field of physical-sports and the mental image people have of themselves. In this respect, this study reflects the objectives of (a) determining the factors affecting social appearance anxiety and (b) testing whether physical activity is a significant determinant of social appearance anxiety. For this purpose, a quantitative study was conducted on a sample of 250 participants; %54 male and %46 female.The tool used is the Turkish version of the “Social Appearance Anxiety Scale”. There was a significant difference between social appearance anxiety levels in terms of gender(p<0.05). There was difference between social appearance anxiety levels in terms of doing sport and working status(p<0.05). The results show that those who do sports, women, unemployed, dissatisfied with their height and weight have higher levels of appearance anxiety. In conclusion, body dissatisfaction and attitudes towards appearance are important determinants of appearance anxiety risk among both genders and whether or not they do sports.
Keywords: Anxiety; Social Cohesion; Body Image